Evaluasi Tingkat Kenyamanan Pengunjung di Wisata Alam Sumber Jenon Kecamatan Tajinan - Landu Praing, Robinson; Alfian, Rizki; Akbar, Moch. Azkari Hisbulloh (Universitas Mulawarman, 2025)
Sumber Jenon Natural Tourism Area is a nature-based tourist destination located in Gunungronggo Village, Tajinan District, Malang Regency. The site is renowned for its clear spring water, lush natural atmosphere, and preserved local cultural values, making it an attractive destination for visitors. However, the increase in tourist numbers has not been accompanied by optimal site management, particularly in terms of environmental comfort. Based on field observations and visitor perceptions, several issues were identified, such as the lack of supporting facilities, narrow circulation pathways, and less aesthetically pleasing spatial elements. This study aims to evaluate visitor comfort based on seven physical parameters: thermal comfort, aroma, safety, circulation, cleanliness, aesthetics, and spatial form. The research employed a descriptive quantitative approach through surveys using questionnaires and a rating scale analysis. The results indicate that thermal comfort received the highest score at 77%, followed by aroma at 75%, and safety at 74%. The lowest score was recorded for spatial form at 70%. These findings suggest that while overall comfort is considered good, improvements are still needed, particularly in landscape aesthetics and open space design. This study recommends enhancements in spatial planning, upgrading supporting facilities, and implementing sustainable environmental management to optimize the overall visitor experience.